Penguatan Karakter Pancasilais terhadap Pemuda Melalui Program Leadership Camp: Studi Kuantilatif - Palupi Lindiasari Samputra; Muhammad Akbar Satrio (Societas Dei: Jurnal Agama dan Masyarakat, 2021)
The human character of Pancasila which is based on faith in God. This research aims to identify the nationalist character produced through the Leadership Camp program, measure the level of nationalism character education, and analyze the strategies carried out by the mosque youth organizations at the Al Azhar Youth Leadership Institute in strengthening the nationalist character of youth. The quantitative method with the type of survey to 100 respondents uses EFA and the nationalism character education index. According to students in the Leadership Training, the nationalist leadership they get is integrity, cooperation, character, nationalism, devotion to worship, and independence. Religious nature consists of morals and obedience to worship. The nationalist Character Education index calculation is 92.51%, which means that the program classifies as a high portion of the nationalism character education learning. The best strategy that AYLI can choose is consistency with a program that is already running well.